Navigating the new normal: Examining coattendance in a hybrid work environment - Charpignon, Marie; Yuan, Yuan; Zhang, Dehao; Amini, Fereshteh; Yang, Longqi; Jaffe, Sonia; Suri, Siddharth (Proceedings of the National Academy of Sciences of the United States of America, 2023)
The recent rise of hybrid work poses novel challenges for synchronizing in-office work schedules. Using anonymized building access data, we quantified coattendance patterns among 43k employees at a large global technology company. We used two-way fixed effects regression models to investigate the association between an employee’s presence in the office and that of their manager and teammates. Our analysis shows that employee in-person attendance was 29% higher when their manager was present. Moreover, a 1-SD increase in the share of teammates who were present yielded a 16% increase in the individual employee’s attendance. We also observed greater coattendance among employees who were recently hired, have a Corporate or Operations role, or work in shared office spaces. Thus, we find evidence of some voluntary alignment of work schedules. Companies could bolster such organic coordination by leveraging digital scheduling tools or providing guidance specifically aimed at increasing coattendance.